Rapid tremor migration during few minute‐long slow earthquakes in Cascadia - Gombert, B; Hawthorne, JC (American Geophysical Union, 2023)
Slow earthquakes are now commonly found to display a wide range of durations, moments, and slip and propagation speeds. But not all types of slow earthquakes have been examined in detail. Here we probe tremor bursts with durations between 1 and 30 min, which are likely driven by few minute-long bursts of aseismic slip. We use a coherence-based technique to detect thousands of tremor bursts beneath Vancouver Island in Cascadia. Then we examine 17 of the ruptures by tracking their evolving tremor locations over an 8-km region. We find that tremor migrates at rates of 3–25 m/s: faster than longer tremor bursts. Though some observational biases persist, the short events' speeds appear to fill a gap in the spectrum of observed slow earthquakes. They may provide further evidence that whatever fault zone process creates slow earthquakes, it must allow for faster slip and propagation in smaller ruptures.